PELATIHAN INDENTIFIKASI INDEKS SAHAM USA UNTUK MEMPREDIKSI FLUKTUASI IHSG: LINCOM ANALYSIS PADA NASABAH TYPE SWINGER RELIANCE SURAKARTA - Tri Widianto; Yenni Khristiana; Nugroho Wisnu Murti (STIE AUB Surakarta, 2020)
ABSTRACT Capital market practices in the type of stock instruments undergo a shift in the way of analysis. This is not in line with the theory of stock fundamental analysis which explains that fundamental factors become the main variable in determining stock investment decisions for the long term. Fundamental analysis of stocks takes into account various factors including company performance, macroeconomic analysis and the industrial sector. The fundamental variable of stock analysis is used as a consideration of the investment portfolio of the stock for the long term. Users of these variables are usually the owners of capital with the type of investor. Investor type is the owner of capital with the main purpose of buying shares by expecting stock valuations in the long run and dividends, not short-term capital gains. The need for the development of applied science of technical analysis and fundamental analysis of stock investors who have a form of trading activities on a daily basis generally only conduct transactions on the capital market using speculation from each investor. This of course in terms of education that novice stock investors do must have the same time in obtaining maximum income in the trading stock market This service is carried out on customers of PT Reliance Surakarta. There were 13 training participants, namely customers who became stock investors but did not trade every day for a short period of time. The service was held for 1 day. Expected outputs from the event are expected that after attending the training the participants are expected to be able to carry out fundamental and technical analysis of JCI fluctuations on a daily basisKeywords: Stock index, JCI Fluctuation Prediction, Swinger Type